Exploring genetic variability of Giardia duodenalis and Enterocytozoon bieneusi in raw vegetables and fruits: implications for food safety and public health in Mozambique - Salamandane, Cátia; Lobo, Maria Luísa; Afonso, Sónia; Xiao, Lihua; Matos, Olga (Frontiers in Microbiology, 2023)
Giardia duodenalis and Enterocytozoon bieneusi are etiologic agents of enteric diseases characterized by diarrhea that can progress to chronicity in humans, especially in children and in immunocompromised patients. The present study aims to assess the genetic pattern of G. duodenalis and E. bieneusi detected in vegetables and fruits commercialized in Maputo markets, Mozambique and determine their public health importance. Eight study points were sampled: a farmer zone, a wholesale, four retail markets and two supermarkets in Maputo city, where eight types of horticultural products were purchased.By nested-PCR methods, 2.8% (9/321) and 1.3% (4/321) of samples monitored were positive for G. duodenalis and E. bieneusi, respectively. Based on the analysis of the βgiardin and ITS rRNA sequences of G. duodenalis and E. bieneusi detected, respectively, four different sequences of G. duodenalis (three novel: BgMZ1, BgMZ2, BgMZ3, and one known) all from Assemblage B and three genotypes of E. bieneusi (two novel: EbMZ4 and EbMZ5, and one known: KIN-1) from group 1. These microorganisms were found and characterized for the first time in horticultural products in Maputo markets. All identified G. duodenalis and E. bieneusi display high genetic similarity within their βgiardin and ITS rRNA sequences, respectively, having been clustered into assemblages and genotypes with high zoonotic transmission potential. Our study may represent a relevant step in the understanding of these intestinal pathogens in association with fresh vegetables and fruits for human consumption, for a better and broader "One Health" approach.